The efficacy of game-based learning activities in enhancing L2 vocabulary acquisition among Saudi non-English majoring students - Al-Sofi, Bakr Bagash Mansour Ahmed (Stellenbosch Papers in Linguistics Plus, 2024)
Vocabulary acquisition is a crucial aspect of second language acquisition (SLA). To facilitate this process, many game-based learning (GBL) activities have been integrated into learning materials, including the New Headway Plus books. These books are specifically designed for adult learners of English in the Middle East and North Africa and are used to teach all freshmen at the University of Bisha in Saudi Arabia. This study has four main objectives: to identify the various types of GBL vocabulary activities included in the prescribed textbooks; to examine the extent to which these activities are efficacious in enhancing Saudi students' second language (L2) vocabulary acquisition; to identify students' perceptions of the role of GBL activities in enhancing their psychological factors; and to examine the impact of students' majors on vocabulary aspects and psychological aspects. Data for this study were collected from the selected books, question sheets for midterm and final exams, students' scores in these exams, and a questionnaire administered to 63 Saudi non-English majoring students. The analysis of the results revealed that various GBL activities were incorporated in the prescribed textbooks, such as crossword activities, picture-word and word-word matching, word scrambles, collocations, and categorization, with crosswords being the most prevalent. GBL activities proved to be efficient in enhancing their vocabulary and recalling previously learned words. Additionally, students had a positive perception of the role of these activities in enhancing their psychological factors. While students' majors were found to have a statistically significant impact on vocabulary acquisition, they did not have a statistically significant impact on psychological aspects such as motivation, engagement, self-confidence, interest, shyness, and collaboration. Recommendations are made to enhance students' L2 vocabulary acquisition.